Efisiensi Produksi Usahatani Jagung Pada Sistem Budidaya Olah Tanah Dan Tanpa Olah Tanah Di Kabupaten Lombok Barat - Suryadi, Alwan; Budastra, I Ketut; Hayati, Hayati (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
The objectives of this research are 1). Analyze the level of corn productivity in the OT and TOT systems 2). Analyzing the costs and income of corn farming in the OT and TOT systems, 3). Analyze the factors that influence corn production, 4). Analyzing the efficiency of corn production in the OT and TOT systems, and 5). Analyzing the efficiency of using corn production factors in the OT and TOT systems in West Lombok Regency. This research uses descriptive methods, data collection uses survey techniques. The types of data in this research are quantitative data and qualitative data. The respondents in this study were corn farmers who are members of Gerung District, Sheet District and Sekotong District because these three Districts are the Districts that produce the most corn in West Lombok Regency. The determination of respondents was determined by quota sampling of 90 people, where from each sub-district, 15 farmers were taken using the tillage system and 15 farmers with tillage, who were taken using simple random sampling (simple random sampling) by drawing randomly. Shows that the average cost of corn farming with a tillage system is IDR 33,429,620.05 greater than the cost of corn farming with a no-till system of IDR 29,951,766.48. Production is also the same, OT 11,212.64 Kg and TOT 9,598.44 Kg. and OT income of IDR 13,663,486.65 and TOT 10,323,900.19. The production function equation for the tillage system is as follows: Y = 98,363 + 7285,316 + 10,684 - 23,083 - 0.251 - 1,070 + 67,469 + 96,180 + 148,929 - 5,275 - 0.869. The production function equation for the no-till system is as follows: Y = 376,366 + 1,398 + 56,372 + 33,368 + 1,757 + 17,095 + 513,285 + 591,852 + 648,293 + 7,566 - 112,733. The results of the production efficiency analysis show that the R/C ratio for corn farming with a tillage system is 1.84 and corn farming with a no tillage system is 1.81, which shows that both are efficient in terms of production. The results of the efficiency analysis of the use of production factors in farming with tillage and no tillage systems are at an inefficient level due to the use of production factors which is still high.